Floquet Theory for $q$-Difference Equations - Bohner, Martin; Chieochan, Rotchana (Sarajevo Journal of Mathematics, 2024)
In this paper, we introduce $ω$-periodic functions in quantum calculus and study the first-order linear $q$-difference vector equation for which its coefficient matrix function is $ω$-periodic and regressive. Based on the new definition of periodic functions, we establish Floquet theory in quantum calculus. 2000 Mathematics Subject Classification. 39A13, 34N05, 26E70